Gender differences in restricted and repetitive behaviors and interests in youth with autism. Issue 2 (17th December 2018) - Antezana, Ligia; Factor, Reina S.; Condy, Emma E.; Strege, Marlene V.; Scarpa, Angela; Richey, John A.
Abstract : Previous work has found gender differences in restricted and repetitive behaviors and interests (RRBI) for autism spectrum disorder (ASD). Compared to girls, affected boys have increased stereotyped and restricted behaviors; however much less is known about gender differences in other areas of RRBI. This study aims to identify whether specific RRBI (i.e., stereotyped, self‐injurious, compulsive, insistence on sameness, ritualistic, and restricted), as measured by item‐level data on the Repetitive Behavior Scale‐Revised (RBS‐R), can distinguish girls from boys with ASD. Participants included 615 individuals with ASD (507 boys; 82.4%), ages 3–18 years of age (M = 10.26, SD = 4.20), who agreed to share data with the National Database for Autism Research (NDAR). Multivariate analysis of variance and discriminant function analysis (DFA) were used to determine whether item‐level RBS‐R data could correctly classify cases by gender. DFA results suggest that RBS‐R items significantly differentiate gender. Strongly differentiating RBS‐R items had greater success in correctly classifying affected boys (67.90%) than girls (61.00%). Items that best‐discriminated gender were heightened stereotyped behaviors and restricted interests items in boys and compulsive, sameness, restricted, and self‐injurious behavior items in girls. This study is the first to find that girls with ASD may have increased compulsive, sameness, and restricted RRBI compared to boys. Additionally, findings support heightened self‐injurious behaviors in affected girls. Future research should disentangle whether elevated rates of RRBI in girls are central to the presentation of ASD in girls or an epiphenomenon of the high rates of co‐occurring disorders (e.g., anxiety) noted in girls. Autism Res 2019, 12: 274–283 © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: This study is the first to examine a comprehensive measure of repetitive behavior in children with autism, with findings of increased compulsive, insistence on sameness, and self‐injurious behavior characterizing girls and increased stereotyped and restricted behavior characterizing boys. Future research should determine whether these elevated behaviors in girls are directly part of the autism presentation in girls or symptoms of co‐occurring psychopathology. It is important for autism diagnostic measures to best capture the types of repetitive behavior girls may demonstrate.